Effects of Rumen-Protected Methionine Supplementation on Growth Performance, Nutrient Digestion, Nitrogen Utilisation and Plasma Amino Acid Profiles of Liaoning Cashmere Goats - Wennan Wang; Lisha Ye; Xingtang Dou; Haiying Liu; Di Han (Animals, 2023)
This study determined the effects of rumen-protected methionine (RPM) supplementation on the growth performance, nutrient digestibility, nitrogen (N) utilisation and plasma amino acid profiles of Liaoning cashmere goats during cashmere fibre growth. Twenty-four yearling male cashmere goats (body weight: 35.41 ± 1.13 kg) were randomly assigned to four dietary treatments: a corn–soybean meal basal diet deficient in methionine (negative control, NC) and a basal diet supplemented with 1, 2 and 3 g/kg of RPM. The RPM supplementation quadratically increased the average daily gain (ADG) and decreased the feed to gain ratio (p = 0.001) without affecting the final body weight and dry matter intake. In particular, compared to NC, 2 g/kg RPM supplementation increased the ADG by 35 g/d (p < 0.001) and resulted in the lowest feed to gain ratio (p < 0.001). RPM increased the apparent total tract digestibility of N and decreased the faecal N levels, both in a linear fashion (p = 0.005). Urinary N levels did not have an effect, but the N retention levels increased linearly with PRM (p = 0.032). Moreover, the RPM decreased the plasma urea N levels (p < 0.001) and increased the plasma Met levels quadratically (p < 0.001). In conclusion, RPM supplementation in the diet of cashmere goats can enhance the utilisation of N and improve ADG during the cashmere fibre growing period, and 2 g/kg of RPM in the diet is suggested.